Exploratory Factor Analysis on the Talent Development Environment Questionnaire (TDEQ-5) for Basketball in Indonesia - Kukuh Hardopo Putro; Suharjana Suharjana; Agus Susworo Dwi Marhaendro; Fauzi Fauzi; Danang Wicaksono; Subagyo Irianto; Trisnar Adi Prabowo (Physical Education Theory and Methodology)
Objectives. This study aimed to adapt and measure the level of validity and reliability of the Talent Development Environment Questionnaire (TDEQ-5) for basketball in Indonesia.